Continuous flow nitration of salicylic acid - Kulkarni, Amol A.; Nivangune, Nayana T.; Kalyani, Vishwanath S.; Joshi, Ramesh A.; Joshi, Rohini R. (Organic Process Research & Development, 2008)
Continuous flow nitration of salicylic acid using HNO3/AcOH was studied in the SS316 tubular microreactor. At specific reaction conditions, complete conversion of the reactant was achieved in less than 7 min. It yielded only mononitro derivatives with a higher selectivity of 5-nitrosalicylic acid. Presence of the lower amount of acetic acid in the reaction mixture was seen to be detrimental, leading to precipitation of the desired product (5-nitrosalicylic acid). Reaction at higher temperatures yielded byproducts. The continuous mode operation using the system comprising the microdevices was demonstrated for 2 h with consistent composition at the outlet.

Catalytic synthesis of chalcone and flavanone using Zn-Al hydrotalcite adhere ionic liquid - Kunde, Lalita B.; Gade, Swapna M.; Kalyani, Vishwanath S.; Gupte, Sunil P. (Catalysis Communications, 2009)
The Claisen-Schmidt condensation of 2'-hydroxy acetophenone and benzaldehyde to chalcone and flavanone show that calcined Zn-Al (6) hydrotalcite is active for this synthesis. Coating of ionic liquid `1-(tri-ethoxy-silyl-propyl)-3-methyl-imidazolium chloride' on Zn-Al hydrotalcites was accomplished employing incipient wetness process and on NaY, NaX, MK-5 and silica gel employing co-condensation methodology. Impregnated IL on calcined Zn-Al (6) catalysts were characterized by XRD, SEM, BET, (13)C and (27)Al NMR analysis and the activity of these catalysts were investigated for chalcone and flavanone synthesis. (27)Al CP MAS NMR technique was used to show that interaction of IL with hydrotalcite modifies the acid-base sites and is responsible for enhancement of catalyst activity. Several aromatic aldehydes were screened to assess the general applicability of the system. (c) 2009 Published by Elsevier B.V.
Keywords: (27)Al CP MAS NMR; chalcone; Claisen-Schmidt condensation; Flavanone; Ionic liquid; Zn-Al hydrotalcite

Continuous flow nitration of benzaldehyde - Kulkarni, Amol A.; Kalyani, Vishwanath S.; Joshi, Ramesh A.; Joshi, Rohini R. (Organic Process Research & Development, 2009)
The nitration of benzaldebyde can be carried out in a safe manner in continuous mode using a microreactor system. Choice of a micromixer was seen to affect the performance of this two-phase reaction significantly The reaction time could he brought down to 2 min by increasing the reaction temperature and thereby taking advantage of higher heat transfer area. The simple T-micromixer is seen to be inefficient for two-phase reactions. Further scope of process intensification is also discussed.